Digital Leadership of Administrators that Affects Teachers’ Skills in the 21St Century in Educational Institutions, Krungthon Tai Group Office Bangkok - Ritmontree, Yasumin; Phrarajavajiranyanamethi (Journal of Dhamma for Life, 2025)
This thesis aims to 1) study the digital leadership of school administrators in Krungthon Tai Group Office Bangkok, 2) study the 21st century skills of teachers in Krungthon Tai Group Office Bangkok, and 3) study the digital leadership of school administrators that affect the 21st century skills of teachers in Krungthon Tai Group Office Bangkok The sample group in this research is 60 schools in the Thonburi South Group, Bangkok, with a total of 341 respondents. The research instrument is a questionnaire. Data analysis is done using a ready-made program. The statistics used in data analysis are frequency, percentage, arithmetic mean, and standard deviation. The hypothesis testing uses multiple regression analysis The results of this research were as follows: 1. The digital leadership of school administrators in Krungthon Tai Group Office Bangkok, is at a high level overall. When considering each aspect, ranked from highest to lowest, they are systematic improvement, followed by culture creation, digital knowledge, digital citizenship, and digital vision. And the last rank is communication, respectively 2. The skills of teachers in the 21st century of educational institutions under the jurisdiction of Bangkok, Thonburi South Group, are overall at a high level. When considering each aspect, ranked from most to least, they are creativity, followed by morality, ethics, and professional law, knowledge, and finally teaching and learning management, measurement, and evaluation, respectively 3. The digital leadership of school administrators that affects the 21st century teacher skills of the Thonburi South Group, Bangkok, are: digital knowledge, systematic improvement, and digital citizenship, with statistical significance at the .05 level, with a multiple correlation coefficient (Multiple R) of .596, or 35.60 percent (R2=3.356), and the predictive equation can be written as follows: Forecast equations in raw score form 𝑌 ′ = 1.117 + .138(X3) + .109(X5) + .336(X6) Forecast equations in standard score form 𝑍’ = .134(X3) + .111(X5) + .356(X6)